Pembuatan Aplikasi Electronic Guided Bible Study Process dengan Biblical Recommendation System - Agus Setiawan Kuswandi; Iwan Nyoto Sandjaja; Alexander Setiawan (Jurnal Infra, 2018)
With technological advancements, human needs can be fulfilled easily. The needs of communication, transportation, and even food can be fulfilled with the help of technology. From the Christian Worldviews, human has basic needs of knowing and having an intimate relationship with his Creator. However, technology isn’t yet used to its full potential to help the fulfillment of this necessity. Christians believe that the Bible is the Word of God which can give answers to the human’s basic needs. Therefore, the writer try to develop a Web Application to help Christians study and understand the Bible. The Application provides verse and information search features with relevant search principle using Elasticsearch. With that features, search results shown based on user needs. On the other hand, user can use application to do Bible Study and give Bible Study material recommendation to the user using Item-based Collaborative Filtering with Item Category Distance and Interestingness Measure algorithm. The testing results of the application shows that the features in this application are working properly and able to help the users to understand the Bible better.